Evaluating the incidence of mix design parameters and compaction on the properties of pervious concrete mixtures for urban pavements: a statistical approach. Issue 3 (February 2019) - Bonicelli, Alessandra; Pérez-Osorio, Andrés; Fuentes, Luis
Abstract: Pervious concrete is an emerging pavement material that allows the percolation of water through its structure. This innovative material offers several environmental benefits, such as reducing water runoff volumes and peak flowrates, enabling the natural recharge of groundwater reservoirs and filtering contaminants in water, among others. Despite the promising environmental advantages of this material, some limitations remain in the fields of application due to its mechanical performance and the limited availability of mix-design guidelines. The current study aimed at investigating the effect of water proportion, cement content and compaction energy on volumetric and mechanical properties of pervious concrete mixtures. The influence of these variables were statistically analyzed and modeled through regressions in order to develop a primal procedure for proportioning. Outcomes from ANOVA showed that all the studied factors significantly contributed to both strength and porosity, being cement/aggregate ratio and compaction energy the most influential. The resulting regression models had fair-to-good coefficients of determination; models were used to generate contour graphs of the material properties that were plotted in order to develop user-friendly mix proportioning schemes.